EKSISTENSI HUKUM ADAT DALAM KONSTITUSI NEGARA PASCAAMANDEMEN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
As a manifestation of our indigenous laws, adat law is an important source in our national legislation. Being aware that the government should recognise both moral values and formal written laws, this article explores the existence of adat law in the Indonesian constitution since our independence to todays Reformasi era.